Shamba shape up series 13 - Ep 21: Passion fruit, beekeeping, chicken brooding, organic manure and financial literacy - Burra, Dharani Dhar; Ramírez Villegas, Julián Armando; Rottmann, Sophie; Galgallo, Diba; Murage, Paul; Campbell, David (2023)
"Shamba Shape Up" is a popular television show in East Africa that focuses on agricultural education and improvement. The show features a team of experts who visit different farms, providing practical demonstrations and advice to farmers on various aspects of agriculture, such as livestock rearing, crop cultivation, farm management techniques, and sustainable practices. It aims to educate and empower farmers with valuable information and skills to enhance productivity, increase yields, and improve their livelihoods. The program combines entertainment with education, using a reality TV format to engage viewers and encourage the adoption of better farming methods. This episode, part of Series 13 focuses on: (i) vermiculture: production of organic manure through earthworms; (ii) chicken brooding: how to look after hatched chickens and learn best practices for brooding Chickens; (iii) how to get the best price for your products in the market; (iv) integrating passion fruit with green manure, and (v) cover crops and bee keeping. The financial literacy content is funded by the Livestock & Climate (L&C) initiative.